Programas educativos para la promoción de la tolerancia. Justificación y orientaciones - Escámez Sánchez, Juan (Revista Española de Pedagogía, 2018)
This article offers a planning of educative actions to promove tolerance in secondary school pupils. It has four main parts: a brief presentation of the old and actual problem about intolerance, the characteristics of the pedagogical speech about tolerance, the assumptions that are used to create the accion proposals and, finally, six programatics lines to articulate activities, methods and contents for the development of tolerance.
Keywords: programas educativos; tolerancia; justificación; orientación; Revista Española de Pedagogía